An unusual cause of focal hand dystonia due to a retained implant of the distal radius - Vaishya, Raju (BMJ Case Rep, 2016)
Focal hand dystonia (FHD) is characterised clinically by a task-specific symptom and typical electromyography findings of a characteristic pattern of cocontraction of the agonist and antagonist muscles of the hand and forearm. The aetiopathogenesis of this condition is still not clear. We present a case of a patient with an unusual aetiology for this condition, in the form of retained hardware in the distal radius. This patient had complete resolution of symptoms after removal of a retained radial plate. Thorough history-taking, clinical examination and necessary investigations are the cornerstones for making a diagnosis of FHD.